Electrocoagulation as an Effective Method to Reduce Microplastic Waste in Water - Anting Wulandari; Fitri Afina Radityani; Ahmad Ramadhani; Kharisma Feri Setiawan; Yusepi Yusepi; Randi Anargya (JURNAL PERIKANAN DAN KELAUTAN, 2026)
Microplastics are small plastic particles (